RBR-Type E3 Ligases and the Ubiquitin-Conjugating Enzyme UBC26 Regulate Abscisic Acid Receptor Levels and Signaling. Issue 4 (7th November 2019) - Fernandez, Maria Angeles; Belda-Palazon, Borja; Julian, Jose; Coego, Alberto; Lozano-Juste, Jorge; Iñigo, Sabrina; Rodriguez, Lesia; Bueso, Eduardo; Goossens, Alain; Rodriguez, Pedro L.
Abstract : Abscisic acid receptors are targeted for degradation by a family of E3 ubiquitin ligases at different subcellular locations, which modulates hormone signaling in plasma membrane, cytosol, and nucleus Abstract: The turnover of abscisic acid (ABA) signaling core components modulates the plant's response to ABA and is regulated by ubiquitination. We show that Arabidopsis ( Arabidopsis thaliana ) RING Finger ABA-Related1 (RFA1) and RFA4 E3 ubiquitin ligases, members of the RING between RING fingers (RBR)-type RSL1/RFA family, are key regulators of ABA receptor stability in root and leaf tissues, targeting ABA receptors for degradation in different subcellular locations. RFA1 is localized both in the nucleus and cytosol, whereas RFA4 shows specific nuclear localization and promotes nuclear degradation of ABA receptors. Therefore, members of the RSL1/RFA family interact with ABA receptors at plasma membrane, cytosol, and nucleus, targeting them for degradation via the endosomal/vacuolar RSL1-dependent pathway or 26S proteasome. Additionally, we provide insight into the physiological function of the relatively unexplored plant RBR-type E3 ligases, and through mutagenesis and biochemical assays we identified cysteine-361 in RFA4 as the putative active site cysteine, which is a distinctive feature of RBR-type E3 ligases. Endogenous levels of PYR1 and PYL4 ABA receptors were higher in the rfa1 rfa4 double mutant than in wild-type plants. UBC26 was identified as the cognate nuclear E2 enzyme that interacts with the RFA4 E3 ligase and forms UBC26-RFA4-receptor complexes in nuclear speckles. Loss-of-function ubc26 alleles and the rfa1 rfa4 double mutant showed enhanced sensitivity to ABA and accumulation of ABA receptors compared with the wild type. Together, our results reveal a sophisticated mechanism by which ABA receptors are targeted by ubiquitin at different subcellular locations, in which the complexity of the ABA receptor family is mirrored in the partner RBR-type E3 ligases.